Combining Stochastic Resonance Vibration With Exergaming for Motor-Cognitive Training in Long-Term Care; A Sham-Control Randomized Controlled Pilot Trial - de Bruin, Eling D.; Baur, Heiner; Brülhart, Yvonne; Luijckx, Eefje; Hinrichs, Timo; Rogan, Slavko (Frontiers in Medicine, 2020)
Purpose Physical and mental functions allow classifying older adults as “Go-Go” (independent functioning); “Slow-Go” (in need of care with a slight handicap); and “No-Go” (in need of care with severe functional limitation). The latter group exhibits reduced exercise tolerance. More recently technology-based motor-cognitive types of training services emerged as a possible training service. This study examined the use of technology including stochastic resonance whole-body vibration and Exergame-dance training for motor-cognitive training in care home dwelling adults. Methods Seventeen older adults (10 women, 7 men, age range: 79-98) were randomly assigned to the intervention (IG, n=9) or the sham group (SG, n=8). IG performed five sets of one-minute whole-body vibration with one-minute rest in between, three times a week for the first four weeks of the training period with varying frequency. From weeks five to eight the Exergame-dance training was conducted after the vibration sessions. SG performed a stochastic resonance whole-body vibration training with the same terms applied, however, with a fixed frequency of 1Hz, Noise 1. From weeks five to eight a passive trampoline-programme of five minutes was applied following the vibration sessions. Primary outcome was the Short Physical Performance Battery (SPPB). Secondary outcomes were the Trail Making Test A and B (TMT A & B) and the Falls Efficacy Scale–International (FES-I). Outcomes were measured at baseline, after four and eight weeks of intervention and at follow-up (4 weeks after the intervention). The non-parametric Puri and Sen rank-order test was applied, followed by an ANOVA for repeated measures to analyse main and interaction effects. Mann-Whitney U-Test was used to determine differences between the groups. Results The post-hoc analysis showed significant effects on the SPPB total score with large effect sizes from baseline to eight weeks (+72%, p=0.005, η2 =0.423). The TMT part B displayed significant improvements with large effect sizes from baseline to eight weeks (+17.5%, p=0.002, η2 =0.779) and to follow-up (+21%, p=0.001, η2 =0.827). Conclusion The technology based eight-week training programme consisting of a combination of stochastic resonance whole-body vibration and Exergame-dance training showed beneficial effects on both physical and cognitive performance in older care home dwelling adults.